Cathodic Behaviour of Nickel in Alcohol Solutions of Electrolytes. (20th July 2016) - Bisztyga, Magdalena; Lelek-Borkowska, Urszula; Proniewicz, Edyta; Banaś, Jacek
Abstract: Cathodic behavior of nickel was studied in anhydrous methanol containing sodium methylate. The behaviour of nickel at low overpotentials is determined by competitive processes, reduction of methanol and formation of surface product. The formation of surface layer is the result of a chemical oxidation of intermediate product (NiOCH3surf ). This reaction in the presence of CH3 O − anions causes the precipitation of the Ni(OCH3 )2 film. The process is accompanied by parallel electrochemical reduction of Ni 2+ evidenced by a "limiting" current in the cathodic area. The methoxy film formation during cathodic polarization of the metal surface was confirmed by surface structure measurements.